2006
DOI: 10.1055/s-2006-947349
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Addition of Organocerium(III) Reagents Derived from 3-Substituted Propargyl Bromides to Aldehydes

Abstract: Abstract:Various cerium allenyl reagents were generated by transmetallation of allenyl Grignard compounds with CeCl 3 and subsequent conversion into homopropargylic alcohols by addition to various aliphatic and aromatic aldehydes. The a-acetylenic alcohols were obtained with regioselectivities and diastereoselectivities up to 98% de in favor of the threo-diastereomers.Key words: lanthanides, organometallic reagents, addition reactions, diastereoselectivity, regioselectivityThe importance of allenic anions in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The importance of γ-butyrolactones in synthetic organic chemistry 85 is the foundation of a useful method for the synthesis of threo-homopropargylic alcohols 38, key intermediates for the synthesis of heterocyclic targets (Scheme 14). 86 The authors found that, after formation of allenyl Grignard compounds/CeCl 3 complexes 37, these reacted with various aliphatic and aromatic aldehydes to give the corresponding homopropargylic alcohols. The alcohol adducts have been obtained with threo/erythro ratios ranging from 65:35 to >98:2, and higher regio-and diastereoselectivities have been achieved in reactions promoted by CeCl 3 than other cerium(III) salts such as Ce(OPr i ) 3 .…”
Section: Addition To Carbonyl Compoundsmentioning
confidence: 99%
“…The importance of γ-butyrolactones in synthetic organic chemistry 85 is the foundation of a useful method for the synthesis of threo-homopropargylic alcohols 38, key intermediates for the synthesis of heterocyclic targets (Scheme 14). 86 The authors found that, after formation of allenyl Grignard compounds/CeCl 3 complexes 37, these reacted with various aliphatic and aromatic aldehydes to give the corresponding homopropargylic alcohols. The alcohol adducts have been obtained with threo/erythro ratios ranging from 65:35 to >98:2, and higher regio-and diastereoselectivities have been achieved in reactions promoted by CeCl 3 than other cerium(III) salts such as Ce(OPr i ) 3 .…”
Section: Addition To Carbonyl Compoundsmentioning
confidence: 99%
“…Reactions of allenyl metals with aldehydes to give the corresponding homopropargylic alcohols have been studied extensively . Various derivatives such as allenyl lithium, magnesium, aluminum, zinc, boron, cerium, or titanium have been successively tested with poor to high regio- and diastereoselectivity, depending on the nature of the allenyl moiety substituent. Excellent and general results have been reported by Marshall for the use of isolated alkyl-substituted allenyl tin derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…Allenyl or propargylic organometallic reagents, 112 such as propargylic lithium, 113 boron, 114 silicon, 115 and tin derivatives, 116 reacted with carbonyl or related compounds, 117 including imine and oxocarbenium ion, 118 giving a-allenic alcohols or related compounds. In addition, a variety of other propargylic/ allenic organometallic reagents including titanium, 119 indium, 120 aluminum, 121 zinc, 122 samarium, 123 cerium, 124 and antimony, 125 have also been found suitable for this reaction. As a special case, aldehydes interacted with alcohols in the presence of Lewis acids forming more electrophilic oxocarbenium ion species, which upon interception by nucleophilic propargyl reagents, such as propargylsilanes, afforded allenyl ether compounds.…”
Section: By Addition Of Propargyl or Allenyl Metallic Intermediates T...mentioning
confidence: 99%